2002
DOI: 10.1021/ic0257726
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light Induced Photocleavage of DNA by a Mixed-Metal Supramolecular Complex:  [{(bpy)2Ru(dpp)}2RhCl2]5+

Abstract: The mixed-metal supramolecular complex, [[(bpy)(2)Ru(dpp)](2)RhCl(2)](PF(6))(5) (bpy = 2,2'-bipyridine and dpp = 2,3-bis(2-pyridyl)pyrazine) coupling two ruthenium light absorbers (LAs) to a central rhodium, has been shown to photocleave DNA. This system possesses a lowest lying metal to metal charge transfer (MMCT) excited state in contrast to the metal to ligand charge transfer states (MLCT) of the bpm and Ir analogues. The systems with an MLCT excited state do not photocleavage DNA. [[(bpy)(2)Ru(dpp)](2)RhC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 42 publications
2
70
0
Order By: Relevance
“…These results suggested a cytotoxic effect of these molecules initially by inhibiting DNA synthesis, which will induce a decrease of protein synthesis resulting in diminished cell survival. This pattern corresponds to the effects described for some platinum or other ruthenium derivatives known to bind to DNA [27][28][29][30][31][32]. Photodynamic studies revealed that the nature of the pyridylporphyrin isomer (3-pyridyl or 4-pyridyl) was more important than the degree of substitution of the tetrapyrrole ring.…”
Section: Discussionsupporting
confidence: 75%
“…These results suggested a cytotoxic effect of these molecules initially by inhibiting DNA synthesis, which will induce a decrease of protein synthesis resulting in diminished cell survival. This pattern corresponds to the effects described for some platinum or other ruthenium derivatives known to bind to DNA [27][28][29][30][31][32]. Photodynamic studies revealed that the nature of the pyridylporphyrin isomer (3-pyridyl or 4-pyridyl) was more important than the degree of substitution of the tetrapyrrole ring.…”
Section: Discussionsupporting
confidence: 75%
“…Metal complexes that exhibit interactions with DNA have been studied with the goals of developing both probes for nucleic acid structures and chemotherapy agents [1][2][3][4][5][6][7][8][9]. Photoinduced cleavage of supercoiled plasmid DNA (pBR 322 DNA) is a very interesting topic in recent years, Swavey et al, reported that the complex [{(bpy) 2 Ru (dpp)} 2 RhCl 2 ] [bpy = 2,2¢-bipyridine and dpp = 2,3-bis(2-pyridyl)pyrazine] can induce photocleavage of DNA in visible light [10], which is the first supermolecular system shown to cleave DNA. A considerable number of ruthenium(II) polypyridyl complexes which can bind to DNA in an intercalative mode have been reported [11][12][13][14]; some of which have been shown to act as ''molecular light switches'' and DNA cleavage reagents.…”
Section: Introductionmentioning
confidence: 99%
“…[25] A related compound with a RhCl 2 group complexed by two Ru(bpy) 2 (dpp) groups {dpp = 2,3-bis(2-pyridyl)pyrazine} was even tested on Vero cells in vitro and showed evidence for cell death at concentrations above 10 µ after illumination at Ͼ460 nm, whereas it was inactive when incubated in the dark (Figure 2b,c). [26,27] Normally, excitation in metal-to-ligand charge transfer (MLCT) bands below 500 nm is used to initiate photoreactions of Ru II complexes. For therapeutic applications, however, a longer excitation wavelength is highly desirable due to deeper tissue penetration in the near-IR region.…”
Section: Ruthenium Complexesmentioning
confidence: 99%